ANALISIS BENTUK JAWABAN DAN FITUR KONTEKSTUAL MATERI RASIO PADA BUKU TEKS MATEMATIKA - Salsabila, Khalisha; Ulfah, Syafika (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study analyzes the format of answers and contextual features in ratio-related questions in mathematics textbooks. Two texts were examined: the Grade 6 Elementary School Mathematics Student Book and the third edition of My Pals Are Here! Maths 6A. This study employed a qualitative approach using document analysis. Data collection was conducted through documentation. Data analysis utilized the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and the drawing and verification of conclusions. The results indicate that the domestically published textbook is dominated by closed-ended questions at 65.4%, while the foreign-published textbook reaches 97.6%, indicating a focus on strengthening procedural skills. In terms of contextual features, both types of books featured a high proportion of realistic application questions—69.1% for domestically published books and 90.5% for foreign-published books; domestically published books also included questions with authentic application features (13.6%), whereas foreign-published books contained no authentic questions. This study concludes that that domestically published textbooks provide stronger opportunities for exploration and relevance to students’ real lives, while foreign-published textbooks place greater emphasis on logical procedures and standardized approaches.